Book review: Seeing Lithics: A Middle-range Theory for Testing for Cultural Transmission in the Pleistocene - Katie Davenport-Mackey (Journal of Lithic Studies, 2015)
Seeing Lithics represents a doctoral thesis submitted to Harvard University by Gilbert Tostevin in 2000. Tostevin is currently a professor of Anthropology at the University of Minnesota and has written extensively on human evolution, lithic technology, Old World archaeology, and Palaeolithic archaeology. These interests can be clearly seen in this book which develops a new theoretical and analytical approach to the study of cultural transmission in the Middle-Upper Palaeolithic transition.